Electrolyte for thermal battery and thermal battery
Patent Information
- Application Number
- JP2023138174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0008】 本発明によれば、温度係数の絶対値がより大きい熱電池用電解液、およびそれを備える熱電池を提供することができる。
Smart Images

Figure 2025032723000002 
Figure 2025032723000003 
Figure 2025032723000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolyte for a thermal battery and a thermal battery. [Background technology]
[0002] In the field of thermal power generation technology, thermal batteries (tertiary batteries) have been developed that utilize temperature changes to continuously extract electrical energy. Tertiary batteries use two types of battery electrode materials with different temperature coefficients of oxidation-reduction potential α (= dV / dT) for the positive and negative electrodes, and these positive and negative electrodes are placed in an electrolyte. When a temperature change is applied to a tertiary battery, an electromotive force difference occurs between the positive and negative electrodes, and thermoelectromotive force can be obtained.
[0003] A known example of a tertiary battery is a thermoelectric generating element in which a first electrode and a second electrode face each other via a single electrolyte, and the first electrode and the second electrode contain a material through which the same metal ions reversibly enter and leave the electrode (see, for example, Patent Document 1). Patent Document 1 describes that a sodium chloride aqueous solution is preferable as the electrolyte. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-073596 A Summary of the Invention [Problem to be solved by the invention]
[0005] The thermoelectromotive force generated by a tertiary battery is proportional to the absolute value of the temperature coefficient of the electrode material. Therefore, in order to obtain a larger thermoelectromotive force, an electrode material with a larger absolute value of the temperature coefficient is desired.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide an electrolyte for a thermal battery having a larger absolute value of the temperature coefficient, and a thermal battery including the electrolyte. [Means for solving the problem]
[0007] The present invention has the following aspects. [1] An electrolyte for a thermal battery comprising a lithium salt or a magnesium salt and a solvent. [2] A thermal battery having a first electrode and a second electrode facing each other with an electrolyte interposed therebetween, The thermal battery, wherein the electrolyte is the electrolytic solution for thermal batteries according to [1]. Effect of the Invention
[0008] According to the present invention, it is possible to provide an electrolyte for a thermal battery having a larger absolute value of the temperature coefficient, and a thermal battery including the electrolyte. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a thermal battery in one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing the results of measuring charge / discharge curves using a three-electrode cell using a saturated aqueous solution of lithium nitrate in Experimental Example 1. [Diagram 3] FIG. 11 is a diagram showing a method for measuring the temperature coefficient for each electrolyte in Experimental Example 2. [Figure 4] FIG. 11 is a diagram showing the relationship between potential and temperature when the temperature coefficient was measured in Experimental Example 2, in the case where the ions to be inserted and removed were lithium ions. [Diagram 5] FIG. 11 is a diagram showing the results of measuring the temperature coefficient in a saturated aqueous solution of lithium nitrate in Experimental Example 2. [Figure 6] FIG. 11 is a diagram showing the results of measuring the temperature coefficient in a saturated aqueous solution of sodium nitrate in Experimental Example 3. [Figure 7] FIG. 13 is a diagram showing the results of measuring the temperature coefficient in a saturated aqueous solution of potassium nitrate in Experimental Example 4. [Figure 8]FIG. 11 shows a summary of the results of measuring the temperature coefficient in a saturated aqueous solution of lithium nitrate in Experimental Example 2, the results of measuring the temperature coefficient in a saturated aqueous solution of sodium nitrate in Experimental Example 3, and the results of measuring the temperature coefficient in a saturated aqueous solution of potassium nitrate in Experimental Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An embodiment of the thermal battery electrolyte and the thermal battery of the present invention will be described. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.
[0011] [Electrolyte for thermal batteries] An electrolyte for a thermal battery according to one embodiment of the present invention contains a lithium salt or a magnesium salt and a solvent.
[0012] Lithium (Li) and magnesium (Mg) have smaller ion sizes than sodium (Na). The ion radius of Na is 0.102 nm, that of lithium is 0.076 nm, and that of magnesium is 0.072 nm. In other words, lithium salts and magnesium salts contain metal ions whose ion sizes are smaller than that of sodium (Na).
[0013] Examples of lithium salts include lithium nitrate (LiNO3), lithium chloride (LiCl), lithium perchlorate (LiCLO4), lithium sulfate (Li2SO4), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). Examples of magnesium salts include magnesium nitrate (Mg(NO3)2), magnesium chloride (Mg(Cl)2), magnesium sulfate (MgSO4), magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI)2), and the like.
[0014] Examples of the solvent include water, propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC).
[0015] The concentration of the electrolytic solution for thermal batteries of this embodiment is preferably 0.1 mol / L or more, and is preferably a concentration at which the electrolytic solution for thermal batteries becomes a saturated solution. When the concentration of the electrolytic solution for thermal batteries is equal to or more than the lower limit, the resistance of the electrolytic solution for thermal batteries does not become too large, and there is no adverse effect when the electrolytic solution for thermal batteries is used in a thermal battery.
[0016] The thermal battery electrolyte of the present embodiment contains a salt containing lithium (lithium salt) whose ion size is smaller than that of sodium, or a salt containing magnesium (magnesium salt) whose ion size is smaller than that of sodium, and therefore has a larger absolute value of the temperature coefficient than an electrolyte containing a sodium salt. Therefore, when the thermal battery electrolyte of the present embodiment is used as an electrolyte for a thermal battery, a larger thermoelectromotive force can be obtained than in a thermal battery using an electrolyte containing a sodium salt.
[0017] [Method of manufacturing electrolytic solution for thermal batteries] The thermal battery electrolyte according to this embodiment can be obtained by dissolving the lithium salt or the magnesium salt in a solvent. The method for dissolving the lithium salt or magnesium salt in the solvent is not particularly limited, and examples thereof include a method in which a mixture of the solvent and the lithium salt or magnesium salt is stirred with a stirring blade or a magnetic stirrer.
[0018] [Thermal battery] Hereinafter, the thermal battery of this embodiment will be described with reference to the drawings. FIG. 1 is a cross-sectional view of the thermal battery of this embodiment. As shown in FIG. 1, the thermal battery 1 of this embodiment includes a unit 5 having a first electrode 2, a second electrode 3, and an electrolyte 4. In the thermal battery 1, the first electrode 2 is provided on one surface 6a of the collector 6, and the second electrode 3 is provided on the other surface 6b of the collector 6, and the first electrode 2 and the second electrode 3 are arranged to face each other through the collector 6. The first electrode 2 and the second electrode 3 are arranged to face each other through a separator 7. The first electrode 2 and the second electrode 3 are arranged to face each other at a predetermined interval through a single electrolyte 4 impregnated in the separator 7. A plurality of units 5 each having the first electrode 2, the second electrode 3, and the electrolyte 4 are stacked so that the first electrode 2 of one unit 5 and the second electrode 3 of the other unit 5 are adjacent to each other through the collector 6. The first electrode 2 and the second electrode 3 are electrically connected through a lead wire 8. A circuit (not shown) or a device (not shown) for extracting the current generated in the thermal battery 1 may be provided in the middle of the lead wire 8. Furthermore, these components are sealed with a laminate film 9.
[0019] The first electrode 2 and the second electrode 3 include a material into which the same metal ions reversibly enter and exit. The first electrode 2 and the second electrode 3 may also include a material into which the same metal ions are precipitated or alloyed.
[0020] The first electrode 2 may contain, in addition to the above electrode materials, a binder resin (binding agent) and a conductive assistant. Examples of the binder resin include polyvinylidene fluoride (PVdF) resin, polytetrafluoroethylene (PTFE) resin, and fluororubber. Examples of the conductive assistant include ketjen black, acetylene black (AB), furnace black, vapor grown carbon fiber (VGCF), and carbon nanotubes.
[0021] As the electrolyte 4, the thermal battery electrolyte solution of the above embodiment is used.
[0022] 1 illustrates an example in which a plurality of units 5 each having a first electrode 2, a second electrode 3, and an electrolyte 4 are stacked in a thermal battery 1 such that the first electrode 2 of one unit 5 and the second electrode 3 of the other unit 5 are adjacent to each other, but the present embodiment is not limited to this. The thermal battery 1 of the present embodiment may be composed of one unit 5 each having a first electrode 2, a second electrode 3, and an electrolyte 4.
[0023] According to the thermal battery 1 of this embodiment, since the electrolytic solution for thermal batteries of the above-mentioned embodiment is used as the electrolyte 4, a larger thermoelectromotive force is obtained than when an electrolytic solution containing a sodium salt is used, and it is possible to convert thermal energy into electrical energy by utilizing the temperature change of the entire battery. EXAMPLES
[0024] The present invention will be described in more detail below with reference to experimental examples, but the present invention is not limited to the following experimental examples.
[0025] [Experimental Example 1] (Preparation of electrodes) A nickel Prussian blue analog was precipitated by mixing aqueous solutions containing 10 mmol / L Na4[Fe(CN)6], 10 mmol / L NiCl, and 4 mol / L NaCl. The precipitate was filtered, thoroughly washed with distilled water, and dried to obtain a powder. The composition of the obtained nickel Prussian blue analogue (Ni-PBA) was analyzed by energy dispersive X-ray spectroscopy (SEM-EDXS). 1.76 Ni[Fe(CN)6] 0.94 As the SEM-EDXS device, a scanning electron microscope JSM-IT200 manufactured by JEOL Ltd. was used. The Ni-PBA powder obtained as described above, acetylene black, and polyvinylidene fluoride (PVdF) resin were mixed in a ratio of 7:2:1, and dispersed in N,N-dimethylformamide solvent to form a slurry, which was then applied onto an indium tin oxide (ITO) electrode and dried overnight in vacuum at 65°C to obtain a Ni-PBA electrode.
[0026] (Adjusting the electrodes) The Ni-PBA electrode obtained above was subjected to a charge / discharge reaction in a saturated lithium nitrate aqueous solution, thereby replacing the sodium ions contained in the electrode with lithium ions, thereby obtaining an electrode for use in an aqueous solution containing a lithium salt. Using a similar method, the sodium ions contained in the electrode were replaced with potassium ions by a charge-discharge reaction in a saturated aqueous potassium nitrate solution, yielding an electrode for use in an aqueous solution containing potassium salt. A three-electrode cell was prepared using the Ni-PBA electrode obtained by electrode preparation as the working electrode, platinum as the counter electrode, and an Ag / AgCl standard electrode as the reference electrode, and using a saturated aqueous solution of lithium nitrate (LiNO3) with a concentration of 6 mol / L, a saturated aqueous solution of sodium nitrate (NaNO3) with a concentration of 5 mol / L, or a saturated aqueous solution of potassium nitrate (KNO3) with a concentration of 3 mol / L as the electrolyte. The charge / discharge curves of the resulting three-electrode cell were measured, and the results are shown in Figure 2. The discharge curve was measured as follows: The potential between the electrodes was measured while a constant current was applied using a charge / discharge device (model: HJ10001SD8, manufactured by Hokuto Denko Corporation).
[0027] [Experimental Example 2] (Measurement of temperature coefficient using lithium electrolyte) The method of measuring the temperature coefficient using a lithium electrolyte is as follows. As shown in FIG. 3, the Ni-PBA electrodes obtained in Experimental Example 1 were held in the first beaker 11 and the second beaker 12, respectively, and a saturated aqueous solution of lithium nitrate was poured therein, and the first beaker 11 and the second beaker 12 were connected with a salt bridge 13 to make them electrically conductive. A temperature difference (ΔT) was applied between the first beaker 11 and the second beaker 12, and the electromotive force (V) generated between the electrodes was measured with a voltmeter 14. At this time, the temperature of the first beaker 1 was kept constant at room temperature (23° C.), the second beaker 12 was placed in a thermostatic chamber, and the temperature of the second beaker 12 was changed by 4° C. to 5° C. between room temperature (23° C.) and 40° C., and was held at each temperature for 15 to 20 minutes. FIG. 4 shows the relationship between the potential and temperature when the temperature coefficient was measured in the case where the ions to be inserted and removed were lithium ions. Figure 5 shows a graph plotting the correlation between temperature change and potential change from Figure 4. The straight line in Figure 5 passes through the origin and is drawn using the least squares method, and the slope of this line is the temperature coefficient α, which is -0.71 mV / K from the average of the temperature increase and decrease.
[0028] [Experimental Example 3] (Measurement of temperature coefficient using sodium electrolyte) An analysis was performed in the same manner as in Experimental Example 2, except that a saturated aqueous solution of sodium nitrate was placed in each of the first beaker 11 and the second beaker 12, instead of the saturated aqueous solution of lithium nitrate. A graph plotting the correlation between the temperature change and the potential change when the sodium ion was the ion to be intercalated and deintercalated is shown in Figure 6.
[0029] [Experimental Example 4] (Measurement of temperature coefficient using potassium electrolyte) An analysis was performed in the same manner as in Experimental Example 2, except that a saturated aqueous solution of potassium nitrate was placed in each of the first beaker 11 and the second beaker 12, instead of the saturated aqueous solution of lithium nitrate. A correlation between the temperature change and the potential change in the case where the potassium ion was inserted and removed was plotted in Fig. 7.
[0030] The results of measuring the temperature coefficient in a saturated aqueous solution of lithium nitrate in Experimental Example 2, the results of measuring the temperature coefficient in a saturated aqueous solution of sodium nitrate in Experimental Example 3, and the results of measuring the temperature coefficient in a saturated aqueous solution of potassium nitrate in Experimental Example 4 are all shown in Figure 8. Furthermore, the temperature coefficient α when the ions to be inserted and removed are lithium ions, sodium ions, and potassium ions is all shown in Table 1.
[0031] [Table 1]
[0032] As shown in Table 1, it was found that the absolute value of the temperature coefficient in a saturated lithium nitrate solution is larger than the absolute value of the temperature coefficient in a saturated sodium nitrate solution or a saturated potassium nitrate solution. Therefore, it is expected that a thermal battery using a saturated lithium nitrate solution as an electrolyte will have a larger thermoelectromotive force than a thermal battery using a saturated sodium nitrate solution or a saturated potassium nitrate solution as an electrolyte.
[0033] [Experimental Example 3] (Measurement of temperature coefficient using magnesium electrolyte) A three-electrode cell was prepared using the Ni-PBA electrode obtained in Experimental Example 1 as the working electrode, platinum as the counter electrode, an Ag / AgCl standard electrode as the reference electrode, and an aqueous solution of magnesium nitrate (Mg(NO3)2) with a concentration of 1 mol / L as the electrolyte. The discharge curve was measured using the obtained three-electrode cell. The discharge curve was measured in the same manner as in Experimental Example 2. The temperature coefficient was measured in the same manner as in Experimental Example 2. When the temperature coefficient α was calculated using a magnesium electrolyte, the temperature coefficient α of a 1 mol / L magnesium nitrate solution was found to be 1.02. In other words, the absolute value of the temperature coefficient in the magnesium nitrate solution was found to be greater than the absolute value of the temperature coefficient in a saturated sodium nitrate solution or a saturated potassium nitrate solution. Therefore, it is expected that a thermal battery using a magnesium nitrate solution as an electrolyte will have a greater thermoelectromotive force than a thermal battery using a saturated sodium nitrate solution or a saturated potassium nitrate solution as an electrolyte. [Industrial Applicability]
[0034] A thermal battery comprising the thermal battery electrolyte of the present invention can be used as a thermoelectric power generation element or a thermoelectric power generation system that converts industrial waste heat, solar heat, human body heat, etc. into electrical energy. Specifically, the thermal battery of the present invention can be used as a stationary thermal power generator, a mobile power generator, a hybrid solar energy power generator, etc. [Explanation of symbols]
[0035] 1 Thermal Battery 2 First electrode 3 Second electrode 4 Electrolytes 5 units 6 Collector electrode 7 Separator 8 Lead Wire 9. Laminating Film
Claims
1. An electrolyte for a thermal battery comprising a lithium salt or a magnesium salt and a solvent.
2. A thermal battery having a first electrode and a second electrode facing each other with an electrolyte interposed therebetween, The thermal battery, wherein the electrolyte is the electrolytic solution for thermal batteries according to claim 1 .
Citation Information
Patent Citations
Thermal power generation element
JP2018073596A